Giant Petroclival Primary Intradural Chordoma: Case Report and Systematic Review of the Literature - Fahad AlOtaibi; Marie-Christine Guiot; Thierry Muanza; Salvatore Di Maio (Journal of Neurological Surgery Reports, 2014)
Abstract